Association study of some immunological traits with layer performances in Rhode Island Red chicken lines* - DAS, ANANTA KUMAR; KUMAR, SANJEEV; RAHIM, ABDUL; KOKATE, LAXMIKANT SAMBHAJI; MISHRA, ANIL KUMAR (The Indian Journal of Animal Sciences, 2015)
This investigation aimed to study association of some immunological traits with layer performances in Rhode Island Red (RIR) chicken lines at experimental layer farm of this institute. Five to six weeks aged pedigreed RIR chicks of selected and control lines were immunized against 1% (v/v) sterile sheep erythrocytes suspension (SRBC) to assess humoral immune response through haemagglutination (HA) test. Serum lysozyme and immunoglobulin- G (IgG) concentrations were estimated through agarose lysoplate and single radial immunodiffusion assays. HA titre, serum lysozyme and IgG concentrations were classified in high, medium and low levels based on their means and standard deviations. Layer performance data under various immunocompetence levels were analyzed by least squares analysis of variance. Pullets having high HA titre and serum IgG levels laid heavier eggs at 40th week of age than those with medium or low levels of HA titre and serum IgG in the selected line. Again, hens of the selected line containing high and medium serum IgG levels also laid heavier eggs at 28th week than those with low IgG level. Birds of the control line containing high serum IgG level had heavier body weights at 20th week of age than those with medium IgG level. This generated some valuable information that might be used in the genetic improvement programme of the chicken production and protection status.